Design Parameters for Ionic Liquid–Molecular Solvent Blend Electrolytes to Enable Stable Li Metal Cycling Within Li–O2 Batteries. (4th May 2021) - Neale, Alex R.; Sharpe, Ryan; Yeandel, Stephen R.; Yen, Chih‐Han; Luzyanin, Konstantin V.; Goddard, Pooja; Petrucco, Enrico A.; Hardwick, Laurence J.
Abstract: Effective utilization of Li‐metal electrodes is vital for maximizing the specific energy of lithium–oxygen (Li–O2 ) batteries. Many conventional electrolytes that support Li–O2 cathode processes (e.g., dimethyl sulfoxide, DMSO) are incompatible with Li‐metal. Here, a wide range of ternary solutions based on solvent, salt, and ionic liquid (IL) are explored to understand how formulations may be tailored to enhance stability and performance of DMSO at Li‐metal electrodes. The optimized formulations therein facilitate stable Li plating/stripping performances, Columbic efficiencies >94%, and improved performance in Li–O2 full cells. Characterization of Li surfaces reveals the suppression of dendritic deposition and corrosion and the modulation of decomposition reactions at the interface within optimized formulations. These observations are correlated with spectroscopic characterization and simulation of local solvation environments, indicating the persistent importance of DMSO–Li + ‐cation interactions. Therein, stabilization remains dependent on important molar ratios in solution and the 4:1 solvent‐salt ratio, corresponding to ideal coordination spheres in these systems, is revealed as critical for these ternary formulations. Importantly, introducing this stable, non‐volatile IL has negligible disrupting effects on the critical stabilizing interactions between Li + and DMSO and, thus, may be carefully introduced to tailor other key electrolyte properties for Li–O2 cells. Abstract : The stability of dimethyl sulfoxide (DMSO) electrolytes for Li‐metal cycling and full Li–O2 cells is optimized through formulation of ternary blends with ionic liquid and Li‐salt. The DMSO–Li + solvation interactions, probed via spectroscopy and simulation, are responsible for impeding reductive decomposition of DMSO at high concentrations, while the ionic liquid cation only spectates on the stabilization proceedings.